Systematic Literature Review: Efektivitas Media Edukasi Praktik Sadari (Pemeriksaan Payudara Sendiri) Pada Remaja - Nailal Ulya; Friska Realita (Journal of Health, Medical, and Psychological Studies, 2026)
Breast cancer is the second highest cancer case after lung cancer. In 2022, there was an increase of 2.31 million breast cancers worldwide. Meanwhile, in Indonesia, cancer cases rank first from the total cancer cases in Indonesia, which is 16.6% or 65,858 cases of breast cancer. Breast cancer which increases every year is due to delays in breast cancer diagnosis. Counseling or providing education about breast self-examination (BSE) in various ways will increase early detection of breast cancer. The purpose of this study was to determine the effectiveness of various educational media for BSE practices. The method used is the literature review method from several articles, 2 international articles indexed by Scopus and 8 national articles indexed by Sinta. Based on the 10 articles reviewed, the results showed that there are various educational media, both through electronic media and print media, that can increase the knowledge and skills of young women in doing BSE. It was concluded that audiovisuals, drama, power point, electronic media, videos, leaflets, booklets, demonstrations, Instagram, calendars, Android-based, and via zoom media had an effect on increasing BSE knowledge and skills.